Citra Merek Hijau Terhadap Loyalitas Merek: Peran Mediasi Kepercayaan Merek, dan Persepsi Nilai - Rahayu, Sri; Vedy, Nabila Kharimah; Gumanti, Miswan (JURNAL ILMIAH MANAJEMEN & BISNIS, 2025)
Purpose – This study aims to analyse the influence of green brand image, brand trust, and value perception on brand loyalty. In addition, to test the role of brand trust and value perception as a mediator of the influence of green brand image on brand loyalty.Methodology – This study uses a quantitative approach. Primary data were obtained through the distribution of questionnaires online and offline. The population of this study is students who use laptops at various campuses in the Special Region of Yogyakarta. A total of 222 respondents aged 18-25 years participated in this study. The data was processed using structural equation modelling, SmartPLS.Findings - Green brand image has a significant effect on brand trust, value perception, and brand loyalty. Brand trust has a significant effect on brand loyalty. Brand trust and value perception can be mediators of the influence of a green brand image on brand loyalty.Originality/Novelty – This research examines in depth the role of green brand image, brand trust, and perceived value as an effort to increase brand loyalty, and examines the important role of brand trust and perceived value as mediators in the influence between green brand image and brand loyalty. Implications – Practically contribute to companies in formulating marketing strategies, especially companies with a focus on green brand image, to increase brand loyalty. Theoretical implications: This research contributes to the development of a literature that discusses the image of green brands and other factors that affect brand loyalty.